HYPERTENSIVE DISORDERS OF PREGNANCY: NEONATAL IMPACT - Zegarra, Jaime (2015)
The hypertensive disorders of pregnancy are some of the most serious complications occurring in pregnancy, as they repercute in both mother and fetus. We review the effects of the disease on neonates, including intrauterine growth restriction and repercussions in the hematopoietic, respiratory and central nervous systems, as well as metabolic alterations.